Status pengelolaan perikanan tongkol yang berbasis di PPP Pasongsongan Sumenep, Jawa Timur : suatu pendekatan ekosistem: Status of tongkol fisheries management based in PPP Pasongsongan Sumenep, East Java: an ecosystem approach - Farizi, Wildan Al; Wardani, Mentari Puspa; Primyastanto, Mimit; Supriyadi, Supriyadi; Ghufron, Moh; Wijaya, Arsyad Rifai Fajar (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: The increase in the purse seine fishing fleet and the decline in tuna production will have an impact on the decline in CPUE (Catch Per Unit Effort) per year. The CPUE trend that continues to decline every year is feared to have a negative impact on fish resource stocks and even the tendency of overfishing. Therefore, to overcome the existing problems, an integrated approach to fisheries management is needed through the Ecosystem Approach to Fisheries Management (EAFM). This study aims to assess the status and formulate management actions for tuna fisheries based in the Pasongsongan Coastal Fishing Port (PPP), Sumenep Regency. Methods: The types and sources of data used in this research are primary and secondary data. Primary data were collected through survey and observation methods. Interviews were conducted with 40 randomly selected purse seine fishermen respondents, as well as 1 employee of the Sumenep District Fisheries Office. Secondary data were collected through existing data such as tuna catch, number of trips, number of purse seine fleets, fish prices. Analysis was conducted through an indicator approach using the Multi Criteria Analysis (MCA) approach. Results: The results of the analysis show that the institutional domain shows a very good status, while for the domains of fish resources, fishing techniques, and social with good status, then the economic domain has a moderate status. Conclusion: Based on these indicators, the management status of tuna resources based in the Pasongsongan Coastal Fishing Port is generally in good condition.